Magnetohydrodynamic dusty nanofluid flow over a moving plate with two different boundary conditions - Low, Euwing (2023)
Currently, there are different issues related to low thermal conductivity in the conventional heat transfer fluid, such as water, ethylene glycol and oil, in engineering electronic devices. Aiming to overcome this defect in conventional fluid, this research focuses on nanofluid. Furthermore, dust is considered because in real world, impurities exist and it may affect the flow. Therefore, this research studies the flow and heat transfer characteristics of a dusty nanofluid over a moving plate in the presence of magnetohydrodynamic (MHD). Three types of nanoparticles namely Copper Oxide (CuO) , Aluminium Oxide 2 3 (Al O ) and Titanium Oxide 2 (TiO ) are considered. The governing partial differential equations are converted into a system of non-linear ordinary differential equations using a similarity transformation, then the non-linear ordinary differential equations are solved using bvp4c program in MATLAB software. The influence of non-dimensional governing parameters such as magnetic parameters and nanoparticle volume fraction on the velocity and temperature profiles for fluid and dust phases of dusty nanofluids are discussed. Then, the results obtained are analysed by comparing two cases of boundary conditions, which are constant surface temperature and convective boundary condition in terms of efficiency. The results show that CuO has the lowest velocity but highest heat transfer rate on both fluid and dust phase compared to 2 3 Al O and 2 TiO . Besides, the flow with prescribed surface temperature has better heat transfer rate than the flow with convective boundary condition